Are Financial Reports Useful? The Views of New Zealand Public Versus Private Users. Issue 1 (25th July 2018) - Ehalaiye, Dimu; Laswad, Fawzi; Botica Redmayne, Nives; Stent, Warwick; Cai, Lei
Abstract: This study reports on surveys conducted with users of financial reports in New Zealand. We compare findings for users of reports of two types of for‐profit entities, namely those with public accountability (public entities) and those with no public accountability (private entities). The findings indicate that both types of users have similar perceptions regarding the usefulness of financial statements, with the income statement and balance sheet rated as the most useful components. Furthermore, both types of users, especially private users, perceive financial statements as the most important information source for decision making. Public users have a greater interest in supplementary information than private users. The findings of this study contribute to the debate around differential reporting for private companies and have policy implications with regard to the user‐needs approach to accounting standard setting. Abstract : This paper examines perceptions of users of financial reports in public and private for‐profit entities in New Zealand. Results indicate that both user groups perceive financial statements to be useful but private users attribute higher importance to such statements. Both user groups also attribute different weightings to other supplementary information.